When giving is good: Ventromedial prefrontal cortex activation for others’ intentions - Cooper, Jeffrey C. (2010)
In social decision-making, people care both about others’ outcomes and their intentions to help or harm. How the brain integrates representations of others’ intentions with their outcomes, however, is unknown. In this study, participants inferred others’ decisions in an economic game during functional magnetic resonance imaging. When the game was described in terms of donations, ventromedial prefrontal cortex (VMPFC) activation increased for inferring generous play and decreased for inferring selfish play. When the game was described in terms of individual savings, however, VMPFC activation did not distinguish between strategies. Distinct medial prefrontal regions also encoded consistency with situational norms. A separate network, including right temporoparietal junction and parahippocampal gyrus, was more activated for inferential errors in the donation than in the savings condition. These results for the first time demonstrate that neural responses to others’ generosity or selfishness depend not only on their actions but also on their perceived intentions.